Syndrom wypalenia zawodowego w opinii nauczycieli pracujących zdalnie - Monika Mazur-Mitrowska (Edukacja Ustawiczna Dorosłych)
The article presents the results of a survey which explored the impact of distance learning on the experienced level of occupational burnout of teachers. It also examined the main symptoms of burnout and looked for the most common ways of coping with stress and tension. The respondents concluded that the period of distance learning from March to June 2020 had a large or moderate impact on their experience of occupational burnout. They mention the feeling of being overloaded with tasks, permanent stress, and lack of energy as the main outcomes of working remotely. To cope with the tension and stress during that period teachers pursued their passions and interests, took regular walks, kept in touch with relatives and friends, watched movies, listened to music, meditated, sought for psychological counseling, did sports, or took up anti-stress training